Sistem Informasi Distribusi Gas Elpiji 3 Kg Bersubsidi Berbasis Teknologi Blockchain - Mochammad Rizki Romdoni; Naufal Zahir Rizqullah (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2021)
This research is a research conducted to find out how the private blockchain which uses a multichain platform with the architecture developed by [1] can be used for an information system for the distribution of subsidized 3 kg LPG gas, a case study of the city of Tanjungpinang. The research method used to collect data in this study is the method of questionnaires, interviews and documentation to obtain data that is relevant to this research. The questionnaire was used as a research instrument which was distributed to obtain information from sub-agents and the public regarding subsidized 3 kg LPG gas. Meanwhile, interviews were conducted with agents to find out information about subsidized 3 kg LPG gas. For the soft development method, the author uses the waterfall method. In this study, researchers developed a system based on the architectural system developed by [1]. From the results of the analysis carried out, it can be seen that by using a private blockchain multichain platform design architecture [1] in the distribution process of subsidized 3 kg LPG gas by utilizing a good information system, it can record data / information about the distribution of 3 kg LPG gas subsidized so it can be said that the private blockchain which uses a multichain platform with the architecture developed by [1] can be used for the distribution of subsidized 3 kg LPG gas case study of the city of Tanjungpinang.